Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Pada Ud. Budi Jaya Dinamo - Riza Fiandi; Ahmad Albar Tanjung (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this study was to determine whether there is an effect of product quality and price on purchasing decisions at UD. Budi Jaya Dinamo, The sample in this study was 36 people, sampling using incidental sampling technique, namely the technique of determining the sample when coincidentally met at the research place and then used as a sample. Analysis of the data used in this study is to use a structural equation model with smart PLS. The results of this study indicate that partially product quality does not have a positive but significant effect on purchasing decisions and price has a positive and significant effect on purchasing decisions, while simultaneously research on product quality and price does not have a positive effect on purchasing decisions. So with this purchase decision can be improved through the price